Reducing the Blood Pressure–Related Burden of Cardiovascular Disease: Impact of Achievable Improvements in Blood Pressure Prevention and Control. Issue 10 (October 2015) - Hardy, Shakia T.; Loehr, Laura R.; Butler, Kenneth R.; Chakladar, Sujatro; Chang, Patricia P.; Folsom, Aaron R.; Heiss, Gerardo; MacLehose, Richard F.; Matsushita, Kunihiro; Avery, Christy L.
Abstract : Background: US blood pressure reduction policies are largely restricted to hypertensive populations and associated benefits are often estimated based on unrealistic interventions. Methods and Results: We used multivariable linear regression to estimate incidence rate differences contrasting the impact of 2 pragmatic hypothetical interventions to reduce coronary heart disease, stroke, and heart failure (HF) incidence: (1) a population‐wide intervention that reduced systolic blood pressure by 1 mm Hg and (2) targeted interventions that reduced the prevalence of unaware, untreated, or uncontrolled blood pressure above goal (per Eighth Joint National Committee treatment thresholds) by 10%. In the Atherosclerosis Risk in Communities Study (n=15 744; 45 to 64 years at baseline, 1987–1989), incident coronary heart disease and stroke were adjudicated by physician panels. Incident HF was defined as the first hospitalization with discharge diagnosis code of "428." A 10% proportional reduction in unaware, untreated, or uncontrolled blood pressure above goal resulted in ≈4.61, 3.55, and 11.01 fewer HF events per 100 000 person‐years in African Americans, and 3.77, 1.63, and 4.44 fewer HF events per 100 000 person‐years, respectively, in whites. In contrast, a 1 mm Hg population‐wide systolic blood pressure reduction was associated with 20.3 and 13.3 fewer HF events per 100 000 person‐years in African Americans and whites, respectively. Estimated event reductions for coronary heart disease and stroke were smaller than for HF, but followed a similar pattern for both population‐wide and targeted interventions. Conclusions: Modest population‐wide shifts in systolic blood pressure could have a substantial impact on cardiovascular disease incidence and should be developed in parallel with interventions targeting populations with blood pressure above goal.